Metoda Szkoły Kofoeda i możliwości jej adaptacji do edukacji dorosłych w organizacjach pozarządowych - Szymczak, Sławomir (Studia Edukacyjne, 2018)
This article is an attempt to look at the possibility of applying a unique method of social work, called the Kofoed’s School Method, to adults education pursued by non-governmental organizations. The use of the method of vocational activation, developed in the Copenhagen social institution – Kofoed’s School, requires a look at the specificsof the method and its theoretical genesis. The Kofoed’s School focuses mainly on the social integration of the unemployed with the local community, although it is also a place of adult learning.The theoretical foundations of this method have been shown through Danish social pedagogy and its implications for adult education. The proposed adaptation of the Kofoed’s School Method refers to the educational practice towards adults in non-governmental organizations. In addition, the article outlines previous experience in the implementation of the Kofoed’s School Method in non-governmental organizations in Europe, as well as the opportunities that this method brings to adults education.